Postcolonial Trauma Caused by Dehumanization in Esi Edugyan's Washington Black (2018) - Frianda, Septian; Wahyuni, Delvi (Universitas Negeri Padang, 2023)
This analysis explores the issue of Postcolonial trauma caused by dehumanization in the novel